(untitled) - Conway, Eric D. (Baltimore, 1997)
The book is excellent and will serve not only the beginning student but the professional meteorologist as well. Students will be able to follow and understand each topic the book presents, and professionals will find it helpful in refreshing their memory on various aspects of imagery interpretation
Keywords: Remote sensing